Vitamin D Insufficiency Is Associated with Lower Physical Function in Patients with Heart Failure and Diabetes - M. R. Lopes; Paula A. B. Ribeiro; Priscila Ledur; Gabriela C. Souza; Nadine Clausell; Beatriz D. Schaan (Journal of Diabetes Research)
Vitamin D deficiency is frequent among patients with heart failure (HF) and diabetes, disorders associated with exercise intolerance and muscle weakness. This study aims to search for associations between vitamin D sufficiency and physical function indexes in patients with HF and diabetes. A cross-sectional study of 146 HF patients, 39.7% with diabetes, at a Brazilian tertiary outpatient clinic was performed. Patients underwent clinical evaluation, 6-minute walk test (6 MWT), handgrip strength, physical activity level (IPAQ), and biochemical evaluations including serum 25-hydroxyvitamin D. Classification was done according to vitamin D status (≥30 ng/dL, sufficient) and presence/absence of diabetes in vitamin sufficient, no diabetes (DS-C, n=25), vitamin sufficient, diabetes (DS-DM, n=18), vitamin deficient, no diabetes (DD-C, n= 63), and vitamin deficient, diabetes (DD-DM, n=40). Patients age was 55.4 ± 8 yrs; 70.5% had vitamin D deficiency. Clinical characteristics were similar among groups. Total time expended in physical activity was similar among groups (P=0.26). DS-C covered higher distances in the 6 MWT (392 ± 60 m) versus DD-DM (309 ± 116 m); P=0.024. Handgrip strength was similar among groups but tended to lower levels in DD-DM (P=0.074) even after being adjusted to physical activity (P=0.069). Vitamin D deficiency can influence physical function in HF diabetic patients.